Characterization of a Jet Impingement Heat Sink for Power Electronics Cooling. (1st September 2022) - Klinkhamer, C.; Abishek, S.; Iyer, K.L.V.; Balachandar, R.; Barron, R.
Highlights: Heat transfer correlations for a jet impingement heat sink for cooling power electronics are presented. Pressure drop across the jet impingement heat sink investigated. Heat transfer to pressure trade-off is critical for heat sink design. Jet impingement provides good cooling uniformity. Heat transfer is enhanced with decreasing stand-off distance and increasing jet-to-jet spacing. Abstract: Ongoing demand to improve power electronic converters in terms of efficiency, power density, reliability, cost and packaging calls for optimal thermal management. This paper investigates the effectiveness of a jet impingement heat sink consisting of an array of jets impinging discrete heat sources. A mixture of 60 – 40% (by volume) ethylene glycol – water is the coolant used. Through computational simulations and experimentation on a laboratory prototype, the heat transfer and pressure drop of the heat sink is characterized in terms of Reynolds number, Prandtl number, stand-off distance and jet-to-jet spacing. Correlations for area averaged Nusselt numbers and the Euler number are presented. A trade-off between heat transfer and pressure drop performance is further studied. Higher heat transfer rates were obtained with smaller stand-off distances and larger jet-to-jet spacings at the cost of higher pressure drop. Over the range of parameters tested, heat transfer was found to be more sensitive to design changes (maximum variation of 17.3%) compared to pressure drop (<1% variation). An optimal design will consist of a low stand-off distance as this will provide maximum convective heat transfer rates at the cost of minor pressure drop increases and will ensure the heat sink is compact.